2013
DOI: 10.1007/s10995-013-1398-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Community Health Professional Contact Postpartum on Breastfeeding at 3 Months: A Cross-Sectional Retrospective Study

Abstract: This study investigated the effect of any health professional contact and the types of contact new mothers received in the first 10 days post-discharge on breastfeeding rates at 3 months. This cross-sectional retrospective self-report survey was distributed to women who birthed in Queensland, Australia between 1st February and 31st May 2010 at 4-5 months postpartum. Data were collected on pregnancy, birth, postpartum care and infant feeding. Logistic regression was used to assess the relationship between healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In Australia, the national Infant Feeding Guidelines recommend exclusive breastfeeding until around 6 months of age when solid foods are introduced, and continued breastfeeding until 12 months and beyond [ 7 ]. While the rates of breastfeeding in Australia at discharge from hospital are high and rising, from 87% in 2001 to 95.9% in 2010 [ 35 , 36 ], there is a substantial decline in breastfeeding rates in the following weeks and months. In 2010, breastfeeding rates dropped to 75% at 2 months, to 69% at 4 months and to 42.2% at 7–12 months.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the national Infant Feeding Guidelines recommend exclusive breastfeeding until around 6 months of age when solid foods are introduced, and continued breastfeeding until 12 months and beyond [ 7 ]. While the rates of breastfeeding in Australia at discharge from hospital are high and rising, from 87% in 2001 to 95.9% in 2010 [ 35 , 36 ], there is a substantial decline in breastfeeding rates in the following weeks and months. In 2010, breastfeeding rates dropped to 75% at 2 months, to 69% at 4 months and to 42.2% at 7–12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Institutionally directed forms of social support for new mothers have taken a variety of forms, including telephone interventions, automated text messages, self-initiated clinic visits, national helplines and face-to-face gatherings to facilitate peer-to-peer connections (Biggs et al, 2015; Brodribb and Miller, 2013; Gallegos et al, 2014). In Western Australia, participation in local playgroups was found to be associated with higher social capital and offered increased social connection (Strange et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent Queensland study, however, concluded that health professional contact or home visits in the first ten days post-discharge had no significant impact on breastfeeding at three months [43]. The authors acknowledged that there may be other benefits of health professional contact which they did not assess.…”
Section: Discussionmentioning
confidence: 97%